2020
DOI: 10.1177/1470320320907820
|View full text |Cite
|
Sign up to set email alerts
|

Association of angiotensin-converting enzyme insertion/deletion (ACE I/D) and angiotensinogen (AGT M235T) polymorphisms with the risk of obesity in a Tunisian population

Abstract: Objective: This study aims to determine whether genetic variants in ACE I/D and AGT M235T are associated with overweight-obesity and body mass index (BMI) in a Tunisian population. Methods: We designed an age- and sex-matched case-control study. The height and weight were measured and BMI was calculated. A total of 259 overweight-obese patients and 369 healthy controls were genotyped for the ACE I/D and AGT M235T genes using polymerase chain reaction and restriction fragment length polymorphism. Results: ACE I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In the current scenario, the knowledge of ACE2 gene polymorphism in different populations assumes a huge significance. However, although there have been many published reports on the ACE2 gene polymorphism from different parts of the globe, we came across only one report from Saudi Arabia suggesting a link between the ACE2-rs4646994 I/D polymorphism and the obesity [39]. To the best of our knowledge, the current study on the genetic polymorphism ACE2-rs4646994 I/D and ACE2 rs4240157 C > T in the ACE2 gene is the first one from Saudi Arabia and was carried out in the COVID-19 patients with different disease severity/outcomes and healthy controls.…”
Section: Introductionmentioning
confidence: 78%
“…In the current scenario, the knowledge of ACE2 gene polymorphism in different populations assumes a huge significance. However, although there have been many published reports on the ACE2 gene polymorphism from different parts of the globe, we came across only one report from Saudi Arabia suggesting a link between the ACE2-rs4646994 I/D polymorphism and the obesity [39]. To the best of our knowledge, the current study on the genetic polymorphism ACE2-rs4646994 I/D and ACE2 rs4240157 C > T in the ACE2 gene is the first one from Saudi Arabia and was carried out in the COVID-19 patients with different disease severity/outcomes and healthy controls.…”
Section: Introductionmentioning
confidence: 78%
“…The number of studies dealing with the association of lipid metabolism and VDR and AGT genes polymorphism in patients with EAH is limited. Khamlaoui et al indicated the relation of AGT genotypes with dyslipidemia, that is, reliably higher parameters of TC and LDL-C among the ТТ genotype carriers [17]. Borai et al stated that patients with ischemic heart disease present a considerable difference between AGT genotypes concerning HDL-C with the value р < 0.05 [8].…”
Section: Discussionmentioning
confidence: 99%
“…17 Khamlaoui et al reported that the AGT M235T genotype was associated with the serum levels of low-density lipoprotein (LDL) and total cholesterol (TC) and increased the risk of overweight-obesity. 18 Ji et al suggested that AGT rs2493132 was associated with hypertension in the Chinese Han population, indicating that this polymorphism might be a risk factor for CAD. 19 Although the association of AGT gene polymorphisms with serum lipid metabolism and CAD has been investigated in several studies, the exact relationship between AGT gene polymorphism and the risk of NAFLD and CAD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…reported that the AGT M235T genotype was associated with the serum levels of low-density lipoprotein (LDL) and total cholesterol (TC) and increased the risk of overweight-obesity. 18 Ji et al. suggested that AGT rs2493132 was associated with hypertension in the Chinese Han population, indicating that this polymorphism might be a risk factor for CAD.…”
Section: Introductionmentioning
confidence: 99%